Vaccine manufacturing 2 - Gerson, Don (Henry Stewart Talks, 2015)
New vaccines & the need for up-to-date technology, Considerations for manufacturing facilities, Quality systems (The mechanism for regulatory compliance), Large scale, routine manufacturing, Warehousing and distribution of vaccine product
Reviewed at 2023/06/12